Sistem Informasi Rawat Inap Rumah Sakit Umum Daerah Bima - Rolando, Roy; Sukmaaji, Anjik; Sudarmaningtyas, Pantjawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Hospitalization is essential in Bima Hospital. Inpatient services are service activities to patients in the hospital, occupying a bed for the purposes of observation, visit doctor, administration of fluid and drugs. In the period 2000 through to 2012 Party in particular parts of the hospital inpatient having problems processing of patient data. Search history of patient data, frequent loss of patient data. Cost overruns the process of final payment patient. Another problem faced by the hospital is difficult to make regular monthly report.To overcome the obstacles in the hospitalization, the hospital needs information system to registration patient , the estimated cost of care, loss of medical record patient and can be make report for executive, patients and Kemenkes. With this requirement it needs to make hospitalization information system in the RSUD Bima.